Fuel Cell systems in hybrid-electric aircraft - Meindl, Markus; Forster, Fabian; Eckardt, Bernd; März, Martin (European Electrolyser & Fuel Cell Forum (EFCF), 2025)
With their actual power densities, fuel cell systems are too heavy for aviation. The power density of a fuel cell system can be increased by further developing the subcomponents. Intelligent integration of individual components in the aircraft could be a solution. For this purpose, the aircraft dimensions and simulations of 200 nmi and 600 nmi range from an EU project are used. A more granularly divided series connection of fuel cell systems is considered to integrate these systems in the aircraft more intelligently. A smart way is to equip each fuel cell system with a 640 V (323 kW) system voltage and specially integrated DC-DC boost converters. This choice of system voltage and the use of DC-DC boost converters allow for thinner cross-section cables, easier integration of DC-DC converters into the FC systems housing, and increased system redundancy. The overall control of the fuel cell systems can be carried out via low-weight CAN bus low-voltage signal cables, which hardly contribute to the aircraft's weigh
Keywords: EFCF2025; H2; LowTemp. Fuel Cells & Electrolysers; hybrid-electric aircraft; fuel cells; fuel systems; system integration

Technical System Strategy Review to Improve the Medical Examination of Elbow Dislocations - Forster, Fabian; Meindl, Markus; Gehring, Jonas; Mangold, Lucas; Simon, Michael; März, Martin (2026)
The elbow dislocation is the second most common human dislocation. In case of an injury, a fast and correct diagnosis is essential for a good convalescence. The diagnosis depends on the attending doctor's experience and is sometimes subjective. A technical device should assist the doctor during the first and follow-up examination to eliminate this subjectivity. This generates verifiable diagnostics within the usage of tomographic equipment. To reach this goal, this paper describes the first steps of developing this still-unknown system. Therefore, the knowledge of elbow examination was elaborated and transferred to technical requirements. Later, functional groups were built, and technical solutions were compiled. The best-rated solution yields the theoretical functional principle. To verify the principle and to gather further knowledge, prototypes are designed. The physical realization is made with Fused Deposition Modeling. Different actor principles are evaluated. Tests in computer tomography verified the possible use case. A functional test with a skeleton arm model in the technical solution proves its suitability. The requirements are confirmed and missing data are obtained. The application is registered for patent. Improvements are determined and a technical more sophisticated prototype is in progress. Cadaver arm tests are planned to validate the aspects medicall
https://cris.fau.de/converis/publicweb/Publication/354503096
Keywords: elbow; injury; medicine; computer tomography; mechatronics